The Use of Integrated Reporting as a Tool for Enhancing Business Transparency in the Context of Globalization - Bandura, Zvenyslava; Kostash, Tetiana; Imanova, Mehriban (Актуальні питання економічних наук, 2026)
Economic globalization and the growing influence of nonfinancial factors on investment decision-making have intensified requirements for the quality and comparability of corporate reporting. The expansion of international sustainability reporting standards has been accompanied by deregulation trends, which exacerbate the challenge of ensuring comparable and comprehensive information for market participants. The purpose of this study is to provide a theoretical substantiation and assess the potential of integrated reporting as a tool for enhancing corporate transparency under conditions of globalization. The methodological framework is based on comparative and structural analyses of international databases (G250, N100, CDP, S&P CSA), generalization of statistical indicators reflecting the integration of ESG information (Environmental, Social, Governance) into annual reports, examination of industry-specific differences in corporate reporting practices, and evaluation of regulatory transformations in the context of implementing standards developed by the International Sustainability Standards Board (ISSB) and revising the requirements of the EU Corporate Sustainability Reporting Directive (CSRD). The findings demonstrate an increase in the integration of ESG components into corporate reports, reaching 82 percent among G250 companies and 62 percent among N100 companies in 2024. However, the structure of reporting remains uneven, with a predominance of selected ESG components. Regional and sectoral disparities in transparency levels were identified, along with a decline in the use of the Integrated Reporting Framework among the largest companies, while its application increased within the N100 sample. The analysis of regulatory changes indicates that Omnibus simplification in the European Union may reduce CSRD coverage across certain sectors by 50 to 87 percent, potentially limiting data availability for investors. Significant differences in preparedness for disclosing key topics under the European Sustainability Reporting Standards (ESRS) were observed between large corporations and small and medium-sized enterprises, with gaps of up to 30 to 31 percentage points. This disparity contributes to increased information asymmetry within value chains. The conclusions emphasize that integrated reporting should be regarded as a strategic mechanism for coordinating financial and nonfinancial indicators. It has the capacity to strengthen stakeholder trust, mitigate information-related risks, and enhance corporate competitiveness in the global environment.